2023
DOI: 10.1038/s41598-023-40034-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating individual subjective values of emotion regulation strategies

Abstract: Individuals have a repertoire of emotion regulation (ER) strategies at their disposal, which they can use more or less flexibly. In ER flexibility research, strategies that facilitate goal achievement are considered adaptive and therefore are subjectively valuable. Individuals are motivated to reduce their emotional arousal effectively and to avoid cognitive effort. Perceived costs of ER strategies in the form of effort, however, are highly subjective. Subjective values (SVs) should therefore represent a trade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Furthermore, this complex interplay emphasises that a chosen strategy must not only be effectiveanchored in the anticipation of goal achievement, which is the driving forcebut should also require minimal cognitive effort, which is the restraining force. This dynamic interaction resonates with the findings of Scheffel et al (2021Scheffel et al ( , 2023. During these studies, participants were given the opportunity to choose between several strategies and were then asked to provide reasons for their decision.…”
Section: Effects Of Cognitive Effort In the Selection Stagementioning
confidence: 53%
See 4 more Smart Citations
“…Furthermore, this complex interplay emphasises that a chosen strategy must not only be effectiveanchored in the anticipation of goal achievement, which is the driving forcebut should also require minimal cognitive effort, which is the restraining force. This dynamic interaction resonates with the findings of Scheffel et al (2021Scheffel et al ( , 2023. During these studies, participants were given the opportunity to choose between several strategies and were then asked to provide reasons for their decision.…”
Section: Effects Of Cognitive Effort In the Selection Stagementioning
confidence: 53%
“…Troy et al (2018) found no effects of the strategies reappraisal and acceptance on self-reported effort, but on self-reported difficulty. Scheffel et al (2021Scheffel et al ( , 2023 found slight differences in subjective effort between strategies, but above all large inter-individual differences in effort during implementation. This observation is crucial, as effort is costly (Inzlicht et al, 2018).…”
Section: Effects Of Effort In the Implementation Stagementioning
confidence: 93%
See 3 more Smart Citations